(Invited) Highly Robust a-IGZO TFT for Foldable Displays. (18th August 2016) - Lee, Suhui; Billah, Mohammad Masum; Mativenga, Mallory; Jang, Jin
Abstract : We have demonstrated foldable thin-film transistor (TFT) fabricated on a free-standing plastic substrate. With extreme bending machine, the repeated extreme bending stress was applied to the TFTs up to 10, 000 times. When the bending stress is applied perpendicularly to the channel current flow, the performance of conventional TFT degrades significantly after extreme bending stress. However, the bulk accumulation (BA) a-IGZO TFTs have no degradation after being applied extreme bending stress. Therefore, the TFT performance remains the same after repeated bending, indicating that BA TFTs is highly robust and thus can be applied to bendable AMOLED.